Étudiants d’anglais langue seconde et auto-traduction - Sara GREAVES; Marie-Laure SCHULTZE (E-REA)
Many studies have been made of authorial self-translation in the work of writers such as Beckett and Nabokov, but little has been done to consider self-translation as a creative learning resource for language students. This article focuses on its educational value in terms of establishing the self in the language being studied and of receptivity to others, and as a means of reflecting upon authority and legitimacy and the possibility of a renewed, pre-poetic relationship to language.